Structural and Topological Properties of the Most Compact Toroidal-Lattice Communication Networks - Tyrtyshnikov, Oleksii; Mavrina, Maryna; Chernytska, Ilona; Voloshko, Serhii (International Journal of Engineering and Technology, 2018)
In this article a simple analytical description of the structural-topological properties of toroidal-lattice communication networks is proposed, which allows accurately estimate the main topological metrics of the network at the stage of its topological synthesis. It is shown, that with an increase in the size of a toroidal-lattice network, the number of possible variants for its construction (configurations) increases rapidly. Therefore, it is necessary to solve the problem of finding the most compact structure in the process of topological synthesis, taking into account restrictions on the topological cost of the network. A method for searching for such a structure is described. Â Â